Affective Commitment in Questions; Does LMX, POS, and Job Satisfaction being Answer? - Fera Yuliani; Laura Syahrul; Hendra Lukito; Tedi Hidayat (Enrichment : Journal of Management, 2021)
This study aims to examine the role of leader-members exchange and perceived organizational support influence affective commitment, and job satisfaction as mediator. We use stratified proportionate random sampling as data collecting technique then analyze by assisting PLS Smart 3.3 Software. We found the direct effects among LMX and POS on affective commitment and job satisfaction were significant and positively, but surprisingly affective commitment not significantly affected by job satisfaction, and mediating impact of job satisfaction almost have no contributions in the relationship between our predictor variables to outcome